Acquisition of new genes by oral Neisseria. Issue 10 (October 1982) - Ison, C; Glynn, A A; Bascomb, S
Abstract : It is suggested that part of the increased pharyngeal carriage of meningococci reported in patients with gonorrhoea is due to misidentification of gonococci which have been transformed to maltose fermenters by DNA from normal throat flora. The distribution of specific aminopeptidases in strains of gonococci, meningococci isolated from the throat and meningococci from systemic infections is consistent with this view. Gonococci oxidising maltose and gonococci with gamma-L-glutamyl aminopeptidase activity, both factors regarded as typical of Neisseria meningitidis, can be produced in vitro by transformation with DNA from N lactamica and N meningitidis. The clinical and theoretical implications of such changes are discussed.